High‐Resolution Observations of Turbulence Distributions Across Tropopause Folds. Issue 6 (22nd March 2021) - Söder, Jens; Zülicke, Christoph; Gerding, Michael; Lübken, Franz‐Josef
Abstract: In this study, we interpret two vertical turbulence measurements. We acquired these uninterrupted high‐resolution dissipation rate profiles with the balloon‐borne instrument LITOS (Leibniz Institute Turbulence Observations in the Stratosphere) from velocity measurements using a spectral technique. The meteorological situation is characterized using ECMWF's integrated forecast system (IFS) as breaking Rossby waves showing significant tropospheric jets and a developed tropopause fold. In both cases, dissipation rates in the shear zone above the upper‐tropospheric jet are three orders of magnitude larger than below, reaching severe turbulence strengths (1, 000 mW kg −1 ) in a deep tropopause fold and moderate turbulence strengths in a medium tropopause fold (10 mW kg −1 ). These turbulent spots are shown to create a tripole shaped pattern of PV modification across the tropopause. Furthermore, tracer‐tracer correlations exhibit mixing of tropospheric and stratospheric air masses in the medium‐fold case. While the strength of turbulence corresponds to the depth of the tropopause fold, its asymmetric vertical distribution is possibly related to the tropopause fold life cycle. The observed asymmetry in the vertical turbulence distribution is consistent across both tropopause folds and in overall agreement with measured Richardson numbers. In the medium‐fold case however, it is neither expected from conceptual models nor from Richardson numbers in the IFS. This calls for further field campaigns to investigate the role of turbulence and its implications for the meteorological understanding as well as for aviation safety. Plain Language Summary: Tropopause folds are areas where air from higher altitudes is submerged under the jet stream. These areas are important for the vertical exchange of trace gases and are known for creating aviation hazards due to enhanced turbulence. In our study, we use high‐resolution turbulence measurements from balloons to study the phenomenon. For further understanding, these observations are compared to data from weather forecast models. While we generally find a quantitative agreement between our measurements and other studies, the observed turbulence pattern is unexpected: we find turbulence strengths above the jet stream to be 1, 000 times stronger than below. As conceptional models predict a strengthening of tropopause folds due to turbulence, this result has a likely influence on our understanding of the phenomenon as well as it highlights potential hazards for high flying passenger aircraft. Key Points: High‐resolution turbulence measurements show severe (moderate) turbulence strength in deep (medium) tropopause fold Eddy heat fluxes are found to modify potential vorticity distribution across tropopause fold comparable to other studies Unexpectedly, in both cases dissipation rates above the jet are three orders of magnitude larger than below